Sarcoma of the uterus: guideline of the DGGG, OEGGG and SGGG (S2k-Level, AWMF Registry No. 015/074, April 2021) = Uterine Sarkome : Leitlinie der DGGG, OEGGG und SGGG (S2k-Level, AWMF-Registernummer 015/074, April 2021) - Denschlag, Dominik; Ackermann, Sven; Battista, Marco Johannes; Cremer, Wolfgang; Egerer, Gerlinde; Fehr, Matthias; Follmann, Markus; Haase, Heidemarie; Harter, Philipp; Hettmer, Simone; Horn, Lars-Christian; Juhasz-Boess, Ingolf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose: This is an official guideline, published and coordinated by the Germany Society for Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG). Because of their rarity and heterogeneous histopathology, uterine sarcomas are challenging in terms of their clinical management and therefore require a multidisciplinary approach. To our knowledge, there are currently no binding evidence-based recommendations for the appropriate management of this heterogeneous group of tumors. Methods: This S2k guideline was first published in 2015. The update published here is once again the result of the consensus of a representative interdisciplinary committee of experts who were commissioned by the Guidelines Committee of the DGGG to carry out a systematic search of the literature on uterine sarcomas. Members of the participating professional societies achieved a formal consensus after a structured consensus process. Recommendations: 1.1 Epidemiology, classification, staging of uterine sarcomas. 1.2 Symptoms, general diagnostic workup, general pathology or genetic predisposition to uterine sarcomas. 2. Management of leiomyosarcomas. 3. Management of low-grade endometrial stromal sarcomas. 4. Management of high-grade endometrial stromal sarcoma and undifferentiated uterine sarcomas. 5. Management of adenosarcomas. 6. Rhabdomyosarcomas of the uterus in children and adolescents. 7. Follow-up of uterine sarcomas. 8. Management of morcellated uterine sarcomas. 9. Information provided to patients.
Artikel online veröffentlicht: 01. Dezember 2022
Gesehen am 12.10.2023